Mechanical properties of modular prefabricated steel-concrete composite internal joints under cyclic loading. (March 2021) - Wu, Chenglong; Liu, Jiming; Wang, Qihui; Mou, Ben; Pan, Wei
Abstract: To investigate the influence of the key parameters on the mechanical properties of modular prefabricated steel-concrete composite internal joint (MPCIJ), finite element model (FEM) of MPCIJ under cyclic load was established by using the finite element analysis (FEA) software ABAQUS, based on test results. FEA results were then compared with the test hysteresis curves, skeleton curves, and failure mode. Based on the verification of reliability of the numerical model, the influence of different parameters on the structural performance was analyzed. According to test and FEA results, the MPCIJ shear mechanism and bearing capacity calculation formula were proposed. Results showed that MPCIJ bearing capacity and deformation performance increased with increasing axial compression ratio ( n  < 0.45), however, the increase was within 5%. With the increase of concrete strength, the joint bearing capacity and fire resistance and corrosion resistance of joint modules were effectively improved. The recommended width/thickness ratio of the square steel tube should not be less than 17. Reducing the distance between the bolt edges could improve the plastic deformation of the joint module with the recommended value of 25–35 mm. The bolt hole diameter increase should be between 1.5 and 2 mm. MPCIJ bearing capacity increased with increasing thickness of joint cover plate and the peak load increased by about 17%; however, the shear deformation inside the joint module also increased. The shear mechanism of MPCIJ is the 'steel plate shear wall' and 'T-shaped steel frame'. The correctness and reliability of the MPCIJ shear capacity formula were verified. Graphical abstract: Unlabelled Image Highlights: Refined non-linear finite element analysis of MPCIJs is carried out. Verify the correctness of the MPCIJs finite element model. The mechanical performance of MPCIJs with different parameters is analyzed. The shear mechanism and calculation method of MPCIJs are revealed.